Kavi aura kāvya : saṃskrta tathā prakrta ke kaviyoṃ tathā unakī racanāoṃ kā prāmāṇika varṇana - Upadhyaya, Baldeva, 1899- (SAMP early 20th-century Indian books project ;, 1947)
Sanskrit and Prakrit poetry.